PEMBERIAN BEBERAPA JENIS AUKSIN TERHADAP PERTUMBUHAN AKAR EKSPLAN ANGGREK SECARA IN VITRO - Fathurrahman Fathurrahman (UIR Press, 2013)
The aim of this study was to examine the response of using several kinds of auxin (IBA, IAA and NAA) and concentration (1 ppm, 3 ppm, 5 ppm). This research was conducted in the Biotechnology Laboratory of Faculty of Agriculture Riau Islamic University Pekanbaru during three months, starting from August to October 2011. A half of Medium used was Murashige and Skoog (1/2 MS) with the addition of activated charcoal into the formation of Dendrobium orchid roots. The parameters measured were the number of roots in each week (days 7, 14, 21, 28, 35 and 42). The use of different concentrations of IBA had a significant effect on the parameters examined. In this case of use of concentrations of IAA and NAA, the highest yield obtained from 5 ppm IBA could produce the amount of 4.00 roots per explant at the age of 35 days after initiation. The second highest yield was 5 ppm NAA which could produce to about 3,83 roots per explant at the age of 35 days, followed by 5 ppm IAA with production of root to amount 3.16 per explant.